PENINGKATAN KESEJAHTERAAN GURU SENI DI INDONESIA: ANALISIS TANTANGAN STRUKTURAL DAN MODEL PENGUATAN PROFESIONALISME - Tri Danu Satria; Fadillah Annisa (EDUCATIONAL : Jurnal Inovasi Pendidikan & Pengajaran, 2026)
Teacher welfare is a key pillar of quality education, yet arts teachers in Indonesia still face significant structural challenges. This study aims to analyze these systemic barriers and formulate a strategic model for strengthening arts teacher professionalism. Using a qualitative approach with a conceptual-analytical design, this study conducted a literature review of various scientific articles and educational policy documents from the past decade. Content analysis techniques were used to identify patterns of relationships between the concepts of welfare and the arts ecosystem. The findings indicate that the marginal position of arts education in the curriculum, minimal school facilities, and low social recognition are factors that hinder welfare, impacting motivation and professional identity. In particular, unstable employment status contributes to the worsening economic conditions of educators. As a solution, this study offers a model for strengthening professional capital that integrates human, social, and decision-making dimensions through the development of artistic competencies and the expansion of creative community networks. The main conclusion emphasizes that improving arts teacher welfare requires inclusive systemic policy transformation, not simply financial incentives. The integration of pedagogical autonomy and strong institutional support is essential to strengthen the strategic position of art teachers as creative agents to support the sustainability of the quality of art education in Indonesia in a holistic and sustainable manner for the future of the nation by strengthening the pillars of a just, equitable, competitive, and comprehensive national culture.